Architectural Research: Theories, Methods and Analytical Framework - Abhijit Marawar,; Nikhil Mehare, (AG Volumes, 2025)
The review examines research theories and methodologies, and analysis conceptualization of architectural research-based inquiry in architecture and built environment. It identifies a theoretical background of the architectural research such as positivist, interpretivist, and critical, as well as discusses the approaches of qualitative, quantitative, and mixed methods. The paper highlights the relevance of analytical models in organizing research issues, synthesis of theory and empirical data, as well as facilitating design-driven and performance-based research studies. The review highlights the additional importance of interdisciplinary and theoretically-driven approaches in the context of developing rigorous and effective architectural research by drawing focus on social, environmental, technological, and cultural aspects.